Energy-Efficient Task Synchronization for Real-Time Systems - Chen, Ya-Shu; Yang, Chuan-Yue; Kuo, Tei-Wei (IEEE transactions on industrial informatics, 2010)
In the past decade, energy-efficient real-time task scheduling has been widely explored in the form of various optimization problems. This paper considers energy-efficient real-time task synchronization protocols and the overhead of frequency switching in real systems design. We propose the concept of frequency locking to better manage the cost in frequency switching. To minimize the energy consumption and meet the timing constraints, algorithms are presented to assign tasks base frequencies under existing synchronization protocols which are then extended with the frequency locking concept. Finally, a series of extensive simulations is performed and a real case study is presented to evaluate the proposed methodology and obtain comparison studies using different workloads and protocols.